Factors Affecting the Profitability of Sharia Banking - Aris Supriadi; Agus Ismaya Hasanudin; Lia Uzliawati; Anggi Haerani (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2021)
This study aims to examine the factors that affect the Profitability of Islamic banking, such as Corporate Governance (CG), Financing to Deposit Ratio (FDR), Non-Performing Financing (NPF), and Capital Adequacy Ratio (CAR). This research is quantitative. The type of data used in this research is secondary data. Data processing using the multiple linear regression approach. The results showed that Corporate Governance had a significant positive effect on Profitability. Financing to Deposit Ratio has a significant positive effect on Profitability. Non-Performing Financing has a significant negative effect on Profitability. Capital Adequacy Ratio has a significant positive effect on Profitability. Corporate Governance has a positive effect on the Capital Adequacy Ratio. Financing to Deposit Ratio does not have a positive effect on the Capital Adequacy Ratio. Non-Performing Financing has a significant positive effect on the Capital Adequacy Ratio. Corporate Governance does not have a positive effect on Profitability through the Capital Adequacy Ratio. Financing to Deposit Ratio has an effect on Profitability through the Capital Adequacy Ratio. Non-Performing Financing has no effect on Profitability through the Capital Adequacy Ratio. Increasing banking profits, the banking management can take measures such as keeping the NPF in a safe position, maintaining the quality of productive assets, planning and arranging credit evaluations more carefully and selectively by using the principle of prudence.